Vaccine for the Economy. Issue 6 (9th July 2020) - Shestakova, Veronika
Abstract: Given the global pandemic and the imminent economic crisis, it is important to understand what is happening in our economy and what the consequences will be. The world is looking for a vaccine for the pandemic; however COVID‐19 has affected not only the health of people but the health of the economy, and both need to be cured. What will be the vaccine for our economy? The Federal Reserve is introducing what they consider to be stabilizing measures. However, those measures can have negative effects on our economy and the financial system in the future, and it is crucial for us to understand how and why.